U‐shaped response Unifies views on temperature dependency of stoichiometric requirements. (24th March 2020) - Ruiz, Thomas; Koussoroplis, Apostolos‐Manuel; Danger, Michael; Aguer, Jean‐Pierre; Morel‐Desrosiers, Nicole; Bec, Alexandre
Abstract: Temperature and nutrient availability, which are major drivers of consumer performance, are dramatically affected by global change. To date, there is no consensus on whether warming increases or decreases consumer needs for dietary carbon (C) relatively to phosphorus (P), thus hindering predictions of secondary production responses to global change. Here, we investigate how the dietary C:P ratio optimising consumer growth ( TERC:P : Threshold Elemental Ratio) changes along temperature gradients by combining a temperature‐dependent TERC:P model with growth experiments on Daphnia magna . Both lines of evidence show that the TERC:P response to temperature is U‐shaped. This shape indicates that consumer nutrient requirements can both increase or decrease with increasing temperature, thus reconciling previous contradictive observations into a common framework. This unified framework improves our capacity to forecast the combined effects of nutrient cycle and climatic alterations on invertebrate production. Abstract : Temperature and nutrient availability are major drivers of consumer performance dramatically affected by global change. Here, we investigate how the dietary C:P ratio optimizing consumer growth (TERC:P: Threshold Elemental Ratio) changes along temperature gradients by combining a temperature‐dependent TERC:P model with growth experiments on Daphnia magna. Our results indicate that consumer nutrient requirements can both increase or decrease with increasing temperature thus improving our capacity to forecast the combined effects of nutrient cycle and climatic alterations on invertebrate production.